2012
DOI: 10.1021/ac300204z
|View full text |Cite
|
Sign up to set email alerts
|

Contactless NMR Spectroscopy on a Chip

Abstract: Inductively coupled planar resonators offer convenient integration of high-resolution NMR spectroscopy with microfluidic lab-on-a-chip devices. Planar spiral resonators are fabricated lithographically either by gold electroplating or by etching Cu laminated with polyimide. Their performance is characterized by NMR imaging as well as spectroscopy. A single-scan limit of detection LOD(t) = 0.95 nmol s(1/2) was obtained from sample volumes around 1 μL. The sensitivity of this approach is similar to that obtained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
56
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 53 publications
(56 citation statements)
references
References 38 publications
0
56
0
Order By: Relevance
“…37 Ryan et al 8 have demonstrated microfluidic high-resolution NMR spectroscopy (see Fig. 4) using self-resonant, inductively coupled planar micro-coils, 74 which were fabricated from Cu-laminated polyimide sheets.…”
Section: Planar Spiral M-coilsmentioning
confidence: 99%
“…37 Ryan et al 8 have demonstrated microfluidic high-resolution NMR spectroscopy (see Fig. 4) using self-resonant, inductively coupled planar micro-coils, 74 which were fabricated from Cu-laminated polyimide sheets.…”
Section: Planar Spiral M-coilsmentioning
confidence: 99%
“…A variety of planar micro-NMR detector geometries that are compatible with microfluidic devices have been proposed [5,6], including planar spiral coils [7,8], micro-slots [9], Helmholtz pairs [10], and phased array detectors [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…(ii) The wireless transfer of energy (signal) from an MR detector, which is enabled by placing a pick‐up coil which is wired to the spectrometer in close proximity to a non‐wired MR detector. The signal recorded by the MR detector is transferred via inductive coupling to the spectrometer and is typically used to access samples within restricted areas,7, 8, 9, 10, 11, 12, 13 to locally enhance the signal‐to‐noise ratio (SNR),14, 15, 16 or to improve the handling comfort of MR probes 17, 18, 19, 20, 21, 22…”
Section: Introductionmentioning
confidence: 99%